PENINGKATAN KETERAMPILAN MATERI MENULIS PENGGUNAAN SUATU ALAT MELALUI METODE DEMONSTRASI PADA PELAJARAN BAHASA INDONESIA SISWA KELAS V SDN RANCAKALONG - Siti Hayati (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2019)
The final goal of the series of learning processes undertaken by the teacher is the success of the teaching and learning process. In fact, there are still many weaknesses in the process that can result in the failure of the learning process. In essence learning outcomes refer to everything that belongs to students as a result of teaching and learning activities undertaken. Therefore, each subject requires learning outcomes that are different from other subjects. As was the case with learning at the beginning of Semester I of the 2016/2017 Academic Year in class V Rancakalong. In the implementation of learning Indonesian subjects with the subject matter